Pengaruh Disiplin Kerja, Kompetensi Profesional, dan Motivasi Kerja Terhadap Kinerja Guru SMA Negeri 2 Karanganyar - Rascal Indrastoto; Sutarno (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This research phenomenon concerns the suboptimal performance of teachers at SMA Negeri 2 Karanganyar, as evidenced by a decline in the results of the 2024 Teacher Performance Assessment (PKG) compared to the previous year. The purpose of this study was to analyze the significance of the influence of work discipline on teacher performance at SMA Negeri 2 Karanganyar, to analyze the significance of the influence of professional competence on teacher performance at SMA Negeri 2 Karanganyar, and to analyze the significance of the influence of work motivation on teacher performance at SMA Negeri 2 Karanganyar. The population of this study was all 58 teachers at SMA Negeri 2 Karanganyar. This study used saturated sampling, taking all members of the population as samples. Data collection used a questionnaire scored on a 5-point Likert scale. Data analysis used multiple linear regression analysis. The results of the analysis indicate that (1) Work discipline has a significant effect on teacher performance at SMA Negeri 2 Karanganyar, as indicated by a p-value (0.000) <0.05, thus confirming Hypothesis 1. (2) Professional competence has a significant effect on teacher performance at SMA Negeri 2 Karanganyar, as indicated by a p-value of 0.000 < 0.05. Thus, Hypothesis 2 is proven. (3) Work motivation has a significant effect on teacher performance at SMA Negeri 2 Karanganyar, as indicated by a p-value of 0.001 < 0.05. Thus, Hypothesis 3 is proven.